Literary metamorphosis: a corpus-assisted approach to characterisation in The Rouge of the North and “The Golden Cangue” - Xinyu Shi; Libo Huang (Humanities & Social Sciences Communications)
Abstract Based on her Chinese story “Jinsuo Ji”, the renowned bilingual writer Eileen Chang produced two English versions, i.e. The Rouge of the North and “The Golden Cangue”. The basic difference between the two English versions lies in that The Rouge of the North is more of a rewriting, while “The Golden Cangue” is a direct translation. An interesting issue emerges as to how characters are constructed in those two inter-related texts. This study, taking direct speech as an indicator of character portrayal, adopts a corpus-assisted approach to characterisation in the two texts. The study elaborates on the functions fulfilled by direct speech in constructing characters and carries out a comparative analysis of characterisation in the two texts. The results show that, due to distinctive uses of direct speech, there are subtle yet definite differences between The Rouge of the North and “The Golden Cangue” in shaping characters’ verbal prominence, establishing characters’ verbal interactional relationships, and presenting the protagonists’ linguistic features. Devoted to the issue of characterisation in literary metamorphosis, the study demonstrates the multiple functions performed by direct speech in character portrayal and has some implications for improving corpus methods to examine the complexities of characterisation.